2013
DOI: 10.1248/cpb.c12-00791
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Substituted 6-Amino-4-(2,4-dimethoxyphenyl)-[1,2]dithiolo[4,3-<i>b</i>]pyrrol-5-ones and Their Raising Leukocyte Count Activities

Abstract: The design and synthesis of a series of substituted 6-amino-4-(2,4-dimethoxyphenyl)-[1,2]dithiolo[4,3-b]-pyrrol-5-ones are described. All the synthesized compounds were evaluated for raising leukocyte count activities in normal mice. Four compounds (8a, b, d, h) exhibited raising leukocyte count activities close or higher than positive control recombinant human granulocyte colony stimulating factor (rhG-CSF), and some (8e-g, k, p, r) had a moderate effect. Among them, the most potent compound 8a was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Wang and co-workers expanded on the Welichem results with N-aryl substituted analogues by incorporating N-carbonyl groups on the exo-cyclic nitrogen, presumably to improve solubility of the otherwise lipophilic moiety. 87 The original compound, ZL-004, was initially disclosed in the patent literature, with subsequent analogues reported in the primary literature in 2013. While the investigators did not report a naturally occurring DTP, such as holomycin or thiolutin in their assays, they did demonstrate potent elevation of leukocyte counts in normal mice peripheral blood relative to recombinant human granulocyte colony stimulating factor (rhG-CSF) as a positive control.…”
Section: Analogue Synthesis and Activitymentioning
confidence: 99%
“…Wang and co-workers expanded on the Welichem results with N-aryl substituted analogues by incorporating N-carbonyl groups on the exo-cyclic nitrogen, presumably to improve solubility of the otherwise lipophilic moiety. 87 The original compound, ZL-004, was initially disclosed in the patent literature, with subsequent analogues reported in the primary literature in 2013. While the investigators did not report a naturally occurring DTP, such as holomycin or thiolutin in their assays, they did demonstrate potent elevation of leukocyte counts in normal mice peripheral blood relative to recombinant human granulocyte colony stimulating factor (rhG-CSF) as a positive control.…”
Section: Analogue Synthesis and Activitymentioning
confidence: 99%
“…The synthesis procedures for N ‐aryl pyrrothine derivatives are shown in Scheme 1, following the synthesis routes on previous reports with minor modifications (Li, Wever, et al, 2014; Li, Sun, et al, 2014; Tan et al., 2013). The starting material of compound 1 was obtained according to previous procedure (Tan et al., 2013). Compounds 2a – j were synthesized from compound 1 and chlorocarbonate derivatives (R 1 OCOCl) by amidation reaction at room temperature for 3–10 hr.…”
Section: Resultsmentioning
confidence: 99%
“…Natural dithiolopyrrolones exhibit relatively broad‐spectrum antibiotic activity against many Gram‐positive and Gram‐negative bacteria (Qin et al., 2013). In recent years, N ‐aryl pyrrothine derivatives have been reported to have anticancer (Li et al., 2007) and anti‐leukopenia activity (Li, Wever, et al, 2014; Li, Sun, et al, 2014; Tan et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[194][195][196][197][198][199] N-Aryl DTP analogues have been shown antitumor activity 198 and antileukopenia activity. 194,197 N-Aryl DTP with 2,4-dimethoxyphenyl moiety displayed potent antibacterial activity against clinical isolates of MRSA, RRSA, vancomycin-resistant S. aureus (VRSA), and moderately penicillin-resistant S. pneumoniae (MPRSP) with MIC values in the range of 0.125-2 mg mL À1 comparable to the antibiotic rifampin. 195 Previous works also showed that the biosynthetic pathway of DTPs is susceptible to be manipulated by feeding different organic acids or fatty acids to the cultures to modify the lateral acyl chain.…”
Section: Nat Prod Repmentioning
confidence: 99%